Inference of principal species in caustic aluminate solutions through solid-state spectroscopic characterization. Issue 18 (20th April 2020) - Dembowski, Mateusz; Prange, Micah P.; Pouvreau, Maxime; Graham, Trent R.; Bowden, Mark E.; N'Diaye, Alpha; Schenter, Gregory K.; Clark, Sue B.; Clark, Aurora E.; Rosso, Kevin M.; Pearce, Carolyn I.
Abstract : Tetrahedrally coordinated Al(OH)4 − and Al2 O(OH)6 2− have been isolated in the solid-state and interrogated using XRD, NMR, XAS, IR, and Raman. Abstract : Tetrahedrally coordinated aluminate Al(OH)4 − and dialuminate Al2 O(OH)6 2− anions are considered to be major species in aluminum-rich alkaline solutions. However, their relative abundance remains difficult to spectroscopically quantify due to local structure similarities and poorly understood effects arising from extent of polymerization and counter-cations. To help unravel these relationships here we report detailed characterization of three solid-phase analogues as structurally and compositionally well-defined reference materials. We successfully synthesized a cesium salt of the aluminate monomer, CsAl(OH)4 ·2H2 O, for comparison to potassium and rubidium salts of the aluminate dimer, K2 Al2 O(OH)6, and Rb2 Al2 O(OH)6, respectively. Single crystal and powder X-ray diffraction methods clearly reveal the structure and purity of these materials for which a combination of 27 Al MAS-NMR, Al K-edge X-ray absorption and Raman/IR spectroscopies was then used to fingerprint the two major tetrahedrally coordinated Al species. The resulting insights into the effect of Al–O–Al bridge formation between aluminate tetrahedra on spectroscopic features may also be generalized to the many materials that are based on this motif.